(3GdZQa (B02s - (3Ydj fGFd(B, (3GdadGMs ((3YeGf(B:s (3OGQ RgQGf(B,s)
(3GOGQI bSe GdZQa Ch bSe GdJOHjQ GdafObj h Gdgjcd GdJfXjej dg , eOjQI GdJOHjQ GdafObj (B: (3eSDhdjGJgG , ehGUaGJgG hhGLHGJgG , GMJjGWGJ GdCef GdhGLH GJNGPgG ef bHd GdGOGQI h GdeOjdQI , eSGYOI eOjQI GdJOQjH GdafObj , eTQaj GdWhGHb , GdeOQHGJ h YeGd GdfXGaI h GdaQGTjf , ZQa GdHjGVGJ h WQb GdeQGbHI Ydi HjGVGJ GdafOb h CgOGa GdehGRfI , GdeSJfOGJ GdJj JUOQ ef bSe GdJOQjH GdafObj h YdGbI GdbSe HGdGbSGe GdGNQi , bSe GddhfOQj (B( (3Gdechi(B) (3GdeUHZI h GMJjGWGJ GdCef GdhGLH JhaQgG aj bSe GddhfOQj , bSe GdUjGfI h bSe GdegfOSjf(B.s
Keywords: (3GdGOGQIs; (3GdSjGMIs; (3GdafGObs; (3GdafGOb `` GOGQIs